Investigation of factors affecting utilization of MCH and family planning practices in Bay, Laguna using categorical data analysis - Ilano, Isaac A.
This is a study done in Bay, Laguna with the general objective of determining the factors associated with the utilization of MCH services and family planning practices using categorical data analysis. The factors considered in the study are age, education, income and membership in health and health related organization. This study was done using a sample of 337 married women aged 15-44 years who were selected using stratified cluster sampling design. It compared 3 different approaches to answer the different objectives of the study. These approaches are the Chi-Square Test for Independence, The Goodman's log linear model and the Grizzle-Starmer-Kock approach. Results revealed that income was the most significant factor which affect the utilization of MCH services available in the community. However, age was found to be the best determinant in the practice of family planning.